The Development of Property Rights for Intellectual Property - Miglo, Anton (Journal of Economics and Behavioral Studies, 2011)
This article analyzes the development of property rights (PR) for intellectual property (IP). There is a fundamental tension between competition policy and IP. IP rights confer a certain degree of monopoly power on the owner of IP rights. Some authors found that there are too many patents in Biotechnological or Internet industry. The regulation of intellectual property has expanded dramatically in many countries in recent years and competition authorities are increasingly asking for methodological help in determining the duration and scope of patents. The issue has taken on an increased importance and visibility in the wake of the numerous high profile court cases in the pharmaceutical and internet industry. This paper analyzes a model of PR development for IP. We consider an environment where two agents (researchers) decide whether to determine the allocation of PR or work without establishment of property rights. Both agents may be involved both in research and "political" fight for intellectual property. PR can improve the incentive of one party and worsen the incentive of another party. The main results are: 1) PR do not always emerge and; 2) their emergence is more probable when the more productive party has poor political skills.